Critical friends - real time insights for shaping strategy - Johnson, Debbie; Nathan, Geeta; Rahman, Syahirah Abdul (Chapters, 2022)
This chapter focuses on facilitation given by the Innovation Caucus to provide expert academic critique to inform Innovate UK's strategy for UK business innovation. As Innovate UK's strategy developed, it becam e evident that several policy domains needed critical insights and evi dence. An academic critical friend provided the latest academic insigh ts, evidence and wider perspective of the actors in the UK Innovation system, insights of which policy makers often lack. The chapter gave c ase studies of Innovation Caucus' work with Innovate UK in facilitatin g extensive research expertise and helping policy makers to open dialo gue. It also describes 'The Innovators' Breakfast Club', a webinar ser ies organised by Innovation Caucus, co-developed with Innovate UK, whi ch created live face-to-face dialogue between academic experts and Inn ovate UK strategy/policy leads. This example showed how critical frien ds are important in facilitating the initial dialogues needed to build evidence for policy making. The dialogue builds the foundation for a virtuous cycle of learning. The approach provides an opportunity for a cademic experts to gain insights into the priorities and dilemmas faci ng policy makers, to shape future academic research and refine the ski ll set needed to become critical friends.